CCF THPC inaugural issue editorial - Qian, Depai; Panda, Dhabaleswar K. (CCF transactions on high performance computing (Online), 2019)
Nowadays, it is hard to find a corner in our society that has not been influenced or re-shaped by HPC. Because of its crucial importance in social and economic development, HPC has been identified as one of the priority research subjects. [...]we have witnessed tremendous progress on HPC in the past 20 years in China and all over the world. The topics related to HPC include computational methods, parallel algorithms, parallel computer architectures, processor micro-architectures, memory and storage systems, high performance interconnect, efficient power supply, system cooling, reliability, parallel programming, application software development environment, and domain application software, etc.